Linking fibrotic remodeling and ultrastructural alterations of alveolar epithelial cells after deletion of Nedd4-2 - Engelmann, Theresa A.; Knudsen, Lars; Leitz, Dominik; Dürr, Julia; Beers, Michael F.; Mall, Marcus A.; Ochs, Matthias (International journal of molecular sciences, 2021)
Our previous study showed that in adult mice, conditional Nedd4-2-deficiency in club and alveolar epithelial type II (AE2) cells results in impaired mucociliary clearance, accumulation of Muc5b and progressive, terminal pulmonary fibrosis within 16 weeks. In the present study, we investigated ultrastructural alterations of the alveolar epithelium in relation to interstitial remodeling in alveolar septa as a function of disease progression. Two, eight and twelve weeks after induction of Nedd4-2 knockout, lungs were fixed and subjected to design-based stereological investigation at the light and electron microscopic level. Quantitative data did not show any abnormalities until 8 weeks compared to controls. At 12 weeks, however, volume of septal wall tissue increased while volume of acinar airspace and alveolar surface area significantly decreased. Volume and surface area of alveolar epithelial type I cells were reduced, which could not be compensated by a corresponding increase of AE2 cells. The volume of collagen fibrils in septal walls increased and was linked with an increase in blood-gas barrier thickness. A high correlation between parameters reflecting interstitial remodeling and abnormal AE2 cell ultrastructure could be established. Taken together, abnormal regeneration of the alveolar epithelium is correlated with interstitial septal wall remodeling.